NIAT MEMBELI PRODUK SCARLETT: PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA - Alimin, Erina; Ferliyanti , Herlina; Sabri, Sabri; Nouvel, Ahmad; Gurhanawan, Gurhanawan; Susanti, Melly (Creative Research Management Journal, 2023)
Scarlett is one business in the beauty industry that is expanding right now. The purpose of this study is to determine the ways in which product quality, price, and brand image affect customers' inclinations to purchase Scarlett items. This kind of study is informal and quantitative. Random sampling was utilized in the sampling process, and 105 respondents made up the sample. Students utilizing Scarlett goods were the target audience for the traditional survey. Limitations in the research on how interest in buying Scarlett products is influenced by price, product quality, and brand image. Decisions about how many products to buy at once in a Scarlett store may be influenced by the results of this research.